Appreciative Inquiry for Strategic Planning: An Evaluative and Exploratory Case Study of Two Colleges ... - Saretsky, Kelly (Graduate Studies, 2013)
This case study attempts to analyze and assess the experiences of two colleges, both of which have chosen and used Appreciative Inquiry (AI) as their strategic planning methodology. These institutions are The College of the North Atlantic/Qatar (CNAQ)—in Doha, Qatar—and Northern Essex Community College (NECC)—in Haverhill, Massachusetts. The specific purposes of this study were to collect empirical data as an objective assessment of AI’s overall effectiveness; to isolate and define the recurring themes which seemed to have contributed to the success—or the lack of success—of this planning methodology; to identify other impacts that AI may have had on these two college’s communities and campus cultures; and, to look for factors that could potentially lead to the expanded and sustained us of AI within these different environments. The results of the study indicate that Appreciative Inquiry has been an effective strategic planning process as experienced by these two colleges: 91% of NECC survey respondents and ...